Treatment and evaluation of dysphagia rehabilitation especially on suprahyoid muscles as jaw-opening muscles() - Hara, Koji (Jpn Dent Sci Rev, 2018)
In our aging society, the number of patients with dysphagia, which is associated with disease and aging, is rapidly increasing. The swallowing reflex is a complex process that involves coordinated contractions of swallowing muscles. Many researchers have reported that age-related changes, such as frailty and sarcopenia, affect swallowing muscles and contribute to the decline in the swallowing function. Thus, simple, non-invasive evaluation methods and exercises for swallowing muscles in elderly patients with dysphagia are important. Anterior–superior hyolaryngeal elevation during swallowing results from contractions of the suprahyoid muscle, which plays a primary role in opening the upper esophageal sphincter, along with relaxation of the cricopharyngeal muscle and laryngeal closure. Thus, many researchers have studied methods for evaluating and augmenting suprahyoid muscles. On the other hand, some researchers have reported on dysphagia rehabilitation focused on jaw-opening actions, because hyolaryngeal elevation muscles correspond with jaw-opening muscles. In this study, we describe a new dysphagia evaluation method and an exercise that focuses on suprahyoid muscles with application of jaw-opening actions.